Cubic Spline Histopolation* - Kirsiaed, Evely; Oja, Peeter; Shah, Gul Wali (Mathematical Modelling and Analysis, 2017)
Cubic spline histopolation with arbitrary placement of histogram knots and spline knots between them is studied. Classical boundary conditions are used. Histopolating spline is represented with the help of second moments and particular integrals. The systems determining these parameters are investigated in different cases where diagonal dominance in matrices takes place or may be absent.